THE SPIRITUAL JOURNEY OF SÉHU MARADANG IN THE MAKASSARESE VERSION OF THE LONTARAQ SÉHU MARADANG: FROM CASUAL SEX TO INSAN KAMIL (PERFECT HUMAN BEING) - Mustari Mustari (Prosiding Seminar Nasional dan Internasional HISKI, 2023)
It is surprising to read that a character's spiritual journey to the position of human begins with casual sex. It reads on Lontaraq Séhu Maradang (The Story of Sheikh Mardan), a classic literary work in Makassarese that can be classified as biblical or Islamic literature. This script contains the story of a hero's spiritual wanderings named Sheikh Mardan or Indra Jaya, who is permanently colored by making love with women and written in the prose style of the spoken language of a narrator. This story is important to discuss because it is used as a moral teaching but contains deviant behavior. Does this research answer why there is a narrative of free sex in the text of Pau-paunna Raja Séhu Maradang? This research data is taken from The Story of Sheikh Mardan, transliterated and translated by Aburaerah Aief, published by the Ministry of Education and Culture of the Indonesian and Regional Literature Book Publishing Project 1981. The data collection method used is a reading and recording technique, then selected and sorted relevant data, then analyzed and concluded. This study is a type of qualitative-narrative research with an Islamic science approach. The conclusions of this study are: When this work is placed essentially as a literary work, the meaning of free sex that colors the character's spiritual journey must be interpreted with an implied meaning because the character's religious science is gradually heading towards perfection. The four women courted by Sheikh Mardan began with no marriage to the first two women, then steadily married fiqh to the third woman, and inner marriage plus fiqh marriage to the fourth woman. Sex with a recreative function must be interpreted as the pleasure of the world that must be controlled and restored to its purity as a means of offspring.